PERAN DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN DAN PENINGKATAN DAYA SAING ORGANISASI DI ERA DIGITAL - Ahmad Fadillah; Abu Bakar Riziq; Defry Sulaeman; Fahmmi Firmansyah; Gumilang Ali Prayogi; Reza Prasetya (Journal of Research and Publication Innovation, 2025)
This research integrates various conceptual approaches and case studies on the implementation of Management Information Systems (MIS) to support data-driven decision-making in the digital era. The rapid development of information technology has required organizations to manage data and design business strategies swiftly, positioning MIS as a core foundation for digital transformation. This study aims to describe the role of MIS in supporting the decision-making process and to analyze the impact of MIS implementation on improving organizational efficiency and competitiveness. The research also identifies major constraints, such as human resource limitations and data security issues, faced in the application of MIS across various sectors. A qualitative descriptive approach using the literature review method was employed to synthesize findings from six national scientific journals published between 2022 and 2025. The analysis involved data reduction, categorization, and thematic synthesis to construct a unified conceptual framework. The findings indicate that MIS plays a critical role in accelerating managerial planning, control, and performance evaluation processes. Furthermore, the integration of modern technologies like cloud computing, big data analytics, and artificial intelligence (AI) enhances the effectiveness of MIS in supporting organizational digital transformation and evidence-based decision-making. This study asserts that effective and integrated MIS implementation can significantly improve the quality of decisions, productivity, and organizational competitiveness amidst global competition.